PENILAIAN KINERJA PDAM KOTA DENPASAR DAN PDAM KABUPATEN BADUNG BERBASIS BALANCED SCORECARD - Ariasta, I Gede Agus; Krisnadewi, Komang Ayu (E-Jurnal Akuntansi; Vol 12 No 2 (2015), 2015)
PDAM function as a profit-oriented business and as a social institution that should provide water service to the community. This study is a descriptive study aimed to determine the performance of PDAM Kota Denpasar and Badung regency taps based balanced scorecard. This study uses primary data obtained from the questionnaire answers given by the respondents and using secondary data from financial data taps. Variables examined included the performance of the financial perspective, customer perspective the internal business processes, learning and growth perspective. Financial perspective is measured by using the method of value for money, while the customer perspective, internal business processes, learning and growth using with survey metod of customer satisfaction, process service satisfaction, and employee satisfaction.  . Based on this research, it can be concluded Denpasar PDAM performance from the customer perspective, internal business processe , learning and growth, including both categories, while from a financial perspective, especially on the effectiveness ratios obtained results are not good. Performance Badung taps from a financial perspective, the customer is internal business processes, learning and growth , including good category.
Keywords: Balanced Scorecard, Performance, PDAM